Chironomus gelhausi, a new species of surface-mating Chironomus Meigen, 1803 (Diptera: Chironomidae) from Mongolia - Bouchard , R. William Jr.; Hayford, Barbara L.; Ferrington , Leonard C. Jr (Zootaxa, 2022)
The adult male and female of Chironomus gelhausi n. sp. are described from a small lake in western Mongolia. Based on field observations and morphological characters, C. gelhausi is a surface-mating species which has retained the ability to fly. Morphological characteristics associated with surface-mating in this species include apically truncated wings, reduced antennal plume in the male, reduced palps, reduced mid and hind leg length, and enlarged hypopygium. Behavioral observations and morphology of C. gelhausi indicate that this species is a species of Chironomus which has independently evolved morphological characteristics consistent with surface-mating behavior similar to that of Fleuria and other species within Chironomus sensu lato. We can assume that this behavior and the associated morphological characteristics are related to survival in a harsh environment where high winds could displace aerial mating swarms from the larval habitat.